Ancaman Tersembunyi: Risiko Virus pada Gambar Whatsapp dan Upaya Perlindungan Diri - Gilang Rama Permana; Shadam Jodian Saputra; Naufal Imam Hilmy; Lutfi Nur Wahid; Florida Virginia Luan; Sopian Noer Mohamad (PT Jurnal Cendekia Indonesia, 2025)
WhatsAppis one of the most widely used messaging applications because of its ease and speed in exchanging information, including image files. However, behind this convenience, there is a hidden threat in the form of malware insertion through image files. Cybercriminals often use steganography techniques to embed malicious code in images without changing their visual appearance. When the image is downloaded and opened, malware can be activated and attack the user's device. This article discusses the potential dangers of images on WhatsApp, virusinsertion techniques, and protection strategies that can be carried out. The methods used are literature studies and analysis of real incidents, such as the case of the spread of Pegasus spyware. The findings show that low user awareness, automatic download habits, and the use of unofficial applications increase the risk. As a protective measure, users are advised to disable the automatic download feature, routinely update applications, use antivirus, and be careful with files from unknown sources. This article also emphasizes the importance of increasing digital security literacy and innovation in the development of automatic detection features on communication platforms. With a better understanding, users can take preventive steps against cyber attacks that are disguised through visual media.